2018
DOI: 10.1080/02670836.2018.1435483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow on solidification structure of pure aluminium under pulse magneto-oscillation

Abstract: This paper reports on the processing of aluminium melt by pulse magneto-oscillation (PMO) technology. The melt is divided into five layers using a layered isolation device and, after grinding and corrosion, the refining effects of equiaxed crystals are observed to decrease from the centre outwards. The electromagnetic force and flow velocity of the melt were simulated using the ANSYS package, and found to decrease in the same manner as crystal size; i.e. from the centre outwards. It was also found that the mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The main parameters of PMO, including the peak current, the frequency, and the configuration of the PMO coil, can all be easily adjusted and controlled. Refinement effect was better with higher peak current and lower frequency [19,[21][22][23][24][25][26]. PMO treatment shows great promise in the production of heavy steel ingots on an industrial scale [27].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The main parameters of PMO, including the peak current, the frequency, and the configuration of the PMO coil, can all be easily adjusted and controlled. Refinement effect was better with higher peak current and lower frequency [19,[21][22][23][24][25][26]. PMO treatment shows great promise in the production of heavy steel ingots on an industrial scale [27].…”
Section: Introductionmentioning
confidence: 97%
“…This process, known as nucleus drifting, enhances structural refinement [16][17][18]. PMO promotes heterogeneous nucleation near the solid-liquid interface, and the resulting forced convection causes the partly solidified grains to move away from the solid-liquid interface and become randomly distributed throughout the melt [19]. The convection induced by PMO in Al also changes changes the temperature and solution distribution, which encourages the survival and growth of nuclei [20].…”
Section: Introductionmentioning
confidence: 99%
“…Edry et al [11,12] applied a PMO treatment to pure aluminium (99.9% and 99.999% purity) and proposed a cavity crystal billet growth model. Cheng Shumin et al [13,14] studied the effect of electromagnetic parameters on the refinement of a pure aluminium solidification structure with pure aluminium subjected to PMO with a constant input power. The study found that refinement of aluminium grains can be improved with an increase in current intensity.…”
Section: Introductionmentioning
confidence: 99%
“…He Deping [36] et al used a home-made Bridgman apparatus to introduce different interference growth waveforms during the Al-4%Mg dendrite process and discovered that different waveforms gradually enhanced the vibration interference of Al-4%Mg dendrite growth in sequence. Zhong Yuyi et al [37] applied a pulse magnetic oscillation (abbreviated: PMO) waveform to pure aluminium and founded that the corresponding optimal pulse magnetic oscillation waveform changed with mould size. Zhang et al [38] studied the effect of a pulsed magnetic field on the grain refinement of K4169 alloy and concluded that the combined effect of electromagnetic oscillation and melt convection caused by the pulsed magnetic field affected the grain refinement.…”
Section: Introductionmentioning
confidence: 99%
“…PMO promotes heterogeneous nucleation near the solid-liquid interface, and the resulting forced convection causes the partly solidified grains to move away from the solid-liquid interface and become randomly distributed throughout the melt [19]. The convection induced by PMO in Al also coil and melt surface.…”
Section: Introductionmentioning
confidence: 99%